Development and Validation of a Confirmatory Method for the Determination of 12 Coccidiostat Residues in Eggs and Muscle by Means of Liquid Chromatography Coupled to Hybrid High Resolution Mass Spectrometry - Federica Castellani; Matteo Ricci; Maria Novella Colagrande; Giampiero Scortichini; Giorgio Saluti (Separations, 2023)
A confirmatory, highly selective multi-residue method based on liquid chromatography coupled to hybrid high resolution mass spectrometry (LC-Q-Orbitrap) was developed and validated for the determination of 12 regulated coccidiostats in eggs and muscle. Particularly, ionophore antibiotics (lasalocid, maduramicin, monensin, narasin, salinomycin and semduramicin) and synthetic coccidiostats (diclazuril, halofuginone, nicarbazin as 4,4′-dinitrocarbanilide fraction, robenidine and toltrazuril as toltrazuril-sulphone) were included in the method. The sample preparation consisted in the extraction of the analytes from the matrix with acetonitrile, followed by a clean-up step with Oasis® PRiME HLB SPE and a defatting procedure with n-hexane. Validation was successfully performed according to Commission Implementing Regulation (EU) 2021/808, starting from 1 µg kg−1. The procedure was verified through the analysis of a certified reference material (CRM) and the occurrence of the residues was assessed in the context of the Italian National Residue Control Plan (NRCP).